ROLE OF RETICULOCYTE HEMOGLOBIN CONTENT IN DIAGNOSIS OF IRON DEFICIENCY ANEMIA - Pattanayak, Asisha Kumar; Jali, Siba Narayan; Tripathy, Diptimayee; Behera, Nisarg; Behera, Bijaya Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: Anemia is a global problem of immense health significance affecting persons of all ages and economic groups. Iron deficiency anemia (IDA) is the most common type of anemia met with in clinical practice. For IDA diagnosis, estimation and treatment, many indices such as serum iron (SI), total iron binding capacity (TIBC), serum ferritin (SF), and soluble transferrin receptor assay are used. But reticulocyte hemoglobin content (CHr) is called as the gold standard for diagnosing IDA as it is the most valuable screening tool for identifying IDA with a sensitivity of 94% and specificity 80% and differentiates IDA from anemia of systemic disease. The present study was undertaken to evaluate CHr as a most efficient marker in diagnosing IDA. Methods: This prospective observational study was carried out in the Department of General Medicine of M.K.C.G. Medical College and hospital, Berhampur, Odisha, India, from October 2017 to October 2019. Sixty microcytic hypochromic patients of either sex >18 years of age admitted in the medicine ward fulfilling the inclusion and exclusion criteria were included in this study. After taking detailed history and clinical examination, laboratory investigations including complete blood count, SI, serum, ferritin, serum transferrin saturation, TIBC, CHr, and bone marrow aspiration with iron stain were done in all patients. Results: In the study group of 60 patients, 10 (16.66%) patients had mild anemia, 17 (28.33%) had moderate anemia, and 33 (55%) had severe anemia. Mean hemoglobin of the patients was 6.86 g/dL and SD was 1.95 g/dL. Nineteen (31.66% patients) had TIBC in the range of 351–400 μg/dl. Mean±SD of serum TIBC was 333.91±67.26 μg/dL. Thirty-nine patients (65%) had transferrin saturation in the range of 0.1–10%. The mean±SD of the study group was 13.68±3.22%. Fifty (83.33%) patients had SF in the range of 0–100 μg/dL. Twenty-three patients (38.33%) had CHr concentration between 15.1 and 20 pg followed by 19 (31.66%) between 20.1 and 25 pg and 18 (30%) between 25.1 and 30 pg. The mean±SD of this study was 22.14 pg±3.92. Conclusion: CHr is found to be a potential biomarker that can be used to differentiate IDA from other causes of anemia.